Mumārasat al-Sulūk bi Minangkabau: Tarbīq al-Ta’ālim al-Islāmīyah ‘alā al-Thaqāfah al-Maḥallīyah - Denti, Sri (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This article presents discussions about